EUS-FNB with or without on-site evaluation for the diagnosis of solid pancreatic lesions (FROSENOR): Protocol for a multicenter randomized non-inferiority trial. Issue 6 (June 2019) - Crinò, Stefano Francesco; Manfrin, Ermina; Scarpa, Aldo; Baldaque-Silva, Francisco; Carrara, Silvia; De Nucci, Germana; Di Mitri, Roberto; Ginés, Angel; Iglesias-Garcia, Julio; Itoi, Takao; Kitano, Masayuki; Nguyen, Nam Quoc; et al.
Abstract: Background: Rapid on-site evaluation (ROSE) of cytological specimensacquired with EUS-guided fine needle aspiration (EUS-FNA) represents the most accurate available technique to reach a definitive diagnosis in patients with pancreatic solid masses. Recently, needles with high histological yield have been developed for EUS-guided fine needle biopsy (EUS-FNB), with which the need for ROSE can be potentially overcome. Aims: The primary aim is to compare the diagnostic accuracy of EUS-FNB with or without ROSE. The main endpoint will be measured against the gold standard diagnosis (surgical pathology whenever available or diagnostic work-up in agreement with a clinical course of at least six months). Secondary endpoints include: (a) safety; (b) presence of tissue core; (c) quality of specimens; (d) time of the sampling procedure. Reliability of macroscopic on-site evaluation (MOSE) by endosonographers will be also assessed. Methods: FROSENOR is an international randomized non-inferiority ongoing study at sixteen centers in four continents. Eight hundred patients will be randomized in two arms (EUS-FNB + ROSE vs. EUS-FNB alone) and outcomes compared. Sample size has been calculated in order to demonstrate the non-inferiority of FNB alone. Randomization and data collection will be performed online. Discussion: This study will ascertain if ROSE is still needed when performing EUS-FNB of solid pancreatic lesions.